Comparison between furrow and drip irrigation of melon in the São Francisco Region - Abreu, Tania A. de; Olitta, Antonio Fernando L.; Marchetti, Delmar A.B. (Pesquisa Agropecuaria Brasileira, 2014)
In the Semi-Arid Tropic Research Center (EMBRAPA), Petrolina, PE, an experiment of irrigation methods comparison with melon (Valenciano Amarelo, var.) was conducted. Two methods were used: furrow irrigation normally used in the region, and drip irrigation, a new tecnology that was tested, where the main objective was to determine some important factors for irrigation management. The data have shown that drip irrigation furnished the best results at 0.7 atm of soil water level and with one emitter per four plants. These results were based on water use, fruit size, vegetative growth and yield production of melon crop.